Analysis of leadership quality and communication ability towards teacher performance - Kuswati, Eni; Sayuti, Muhammad; Kuat, Tri (International Journal on Education Insight, 2022)
Many factors can make teacher performance more optimal, for example, the leadership quality and communication skills of the school principal. This article aims to: (1) describe the leadership quality of the principal of the Muhammadiyah Oil and Gas Vocational School in Cilacap; (2) describes the communication skills of the head of the Muhammadiyah Migas Vocational School Cilacap; (3) describe the performance of SMK Muhammadiyah Migas Cilacap vocational teachers; (4) determine the influence of the quality of school principal leadership on the performance of SMK Muhammadiyah Migas Cilacap teachers; (5) find out the influence of school principals’ communication skills on the performance of Cilacap Vocational High School Muhammadiyah teachers; and (6) find out the influence of leadership quality and communication skills of principals on the performance of SMK Muhammadiyah Migas Cilacap teachers. This research is a quantitative study using descriptive analysis and multiple regression analysis. The population in this study were 33 teachers in Muhammadiyah Migas Vocational School Cilacap. Data collection techniques used a closed questionnaire method. Descriptive analysis results show that: (1) The quality of the principal’s leadership can be classified in good categories, (2) The communication skills of the principal can be classified in either category; and (3) Teacher performance is included in the classification of good categories. Furthermore, the results of the regression analysis showed that: (1) there was a positive influence on the quality of the principal’s leadership on the teachers’ performance; (2) there is a positive influence of communication skills on the performance of teachers; (3) and there is a positive influence on the quality of the principals’ leadership and communication skills together on the performance of the teachers.